Patient-reported outcomes following neoadjuvant chemotherapy or chemoradiotherapy treatment for esophageal cancer: a scoping review protocol. (June 2017) - Trenerry, Camilla; Peters, Micah D. J.; Corsini, Nadia; Damarell, Raechel A.; Wilson, Carlene; Flight, Ingrid
Abstract : Review objective: The objective of this scoping review is to identify, describe and compare studies investigating patient-reported outcomes (PROs) in esophageal cancer patients following neoadjuvant (preoperative) chemotherapy (CT) and surgery or neoadjuvant chemoradiotherapy (CRT) and surgery. After preliminary searching of the literature and consultation with experts in the fields of esophageal cancer surgery, behavioral science, information systems and scoping review methodology, the following research objectives were defined as follows: To identify, describe and compare the characteristics and timing of PROs, specifically, psychological and somatic quality of life and symptoms, experienced by esophageal cancer patients during and/or following neoadjuvant CT or CRT. To identify and describe the instruments used to measure PROs in esophageal cancer patients following neoadjuvant CT or CRT.